What is the future of Periodontal Medicine? - Ricardo Guimarães FISCHER; Isaac Suzart GOMES FILHO; Simone Seixas da CRUZ; Victor Bento OLIVEIRA; Ronaldo LIRA-JUNIOR; Frank Andrew SCANNAPIECO; Rodrigo Otávio REGO (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract In the last five decades, considerable progress has been made towards understanding the etiology and pathogenesis of periodontal diseases and their interactions with the host. The impact of an individual periodontal condition on systemic homeostasis became more evident because of this knowledge and prompted advances in studies that associate periodontitis with systemic diseases and conditions. The term Periodontal Medicine describes how periodontal infection/inflammation can affect extraoral health. This review presents the current scientific evidence on the most investigated associations between periodontitis and systemic diseases and conditions, such as cardiovascular diseases, diabetes, preterm birth and low birth weight, and pneumonia. Additionally, other associations between periodontitis and chronic inflammatory bowel disease, colorectal cancer, and Alzheimer's disease that were recently published and are still poorly studied were described. Thus, the aim of this review was to answer the following question: What is the future of Periodontal Medicine? Epidemiological evidence and the evidence of biological plausibility between periodontitis and general health reinforce the rationale that the study of Periodontal Medicine should continue to advance, along with improvements in the epidemiological method, highlighting the statistical power of the studies, the method for data analysis, the case definition of periodontitis, and the type of periodontal therapy to be applied in intervention studies.